A Universal Language Translator: Is This the Future or the Doom of Language Learning? - Andre Syafrony; Vica Ananta Kusuma (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2022)
Artificial Intelligence-based universal language translation system allows users in the Metaverse to better communicate with each other. Meta points to construct an all-inclusive dialect interpretation framework to permit clients to relate to others within the Metaverse without stressing almost dialect obstructions. Zuckerberg uncovered that Meta is working on building an AI-powered "all-inclusive discourse interpreter" for the Metaverse that will work for everybody within the advanced world. This venture points to streamline clients intelligent who speak distinctive dialects within the computerised universe with the assistance of AI. This paper will consider how virtual realities can affect and affect language learning. On the one hand, virtual realities could benefit people trying to learn second languages by providing virtual experiences that we could share with people who speak other languages. We could learn from other people, and they could learn from us, by "total immersion" in such shared experiences. On the other hand, virtual realities could remove the motivation from many people to learn second languages at all by providing nearly simultaneous. These two views will be argued further.